Elastic and inelastic angular distributions of the 7Li+120Sn system for energies near the Coulomb barrier. (5th April 2016) - Zagatto, V A B; Oliveira, J R B; Gasques, L R; Alcántara-Núñez, J A; Duarte, J G; Aguiar, V P; Medina, N H; Seale, W A; Pires, K C C; Freitas, A; Lubian, J; Shorto, J M B; et al.
Abstract: The reaction of 7 Li+ 120 Sn has been measured at bombarding energies of 21, 24 and 27 MeV. The 2 + → 0 + γ -ray transition in 120 Sn was observed and the angular distribution for the 2 + excited state was obtained. Coupled channels and coupled-reaction channels calculations, including the dynamical polarization potential due to the projectile break-up, obtained from continuum discretized coupled channel calculations, were performed. The comparison between the existing experimental elastic angular distribution with the coupled-reaction channels calculations indicates that the 1n stripping transfer is the most intense channel to be coupled and the 2n stripping reaction occurs sequentially rather than directly, however, further data must be analyzed to confirm this indication. The experimental elastic and inelastic scattering data were well described by the calculations, but some discrepancies in these channels may indicate the need for corrections to the nuclear potential and/or the necessity to incorporate further channels.